2019
DOI: 10.1186/s11658-018-0129-6
|View full text |Cite
|
Sign up to set email alerts
|

MiR-219-5p suppresses cell proliferation and cell cycle progression in esophageal squamous cell carcinoma by targeting CCNA2

Abstract: BackgroundWe investigated the potential regulatory role of miR-219-5p in esophageal squamous cell carcinoma (ESCC) and looked at the underlying mechanisms in ESCC.MethodsReal-time PCR was used to determine the levels of miR-219-5p in ESCC tissues and cell lines. The effects of miR-219-5p and cyclin A2 (CCNA2) on cell proliferation and cell cycle progression were evaluated using MTT, colony formation and flow cytometry assays with ESCC cell lines EC9706 and TE-9. Bioinformatics techniques and the luciferase rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…CCNA2 (cyclin A2) is a cyclin accumulated in G1 phase and plays a regulatory role in the transitional period of G1/S and G2/M (Krasnov et al, 2017). Published literature has reported that CCNA2 functions on various cancers, like colorectal cancer (Huang et al, 2017), liver cancer (Yang et al, 2016), breast cancer (Gao et al, 2014), cervical cancer , and EC (Ma, 2019). In the present study, we found that miR-29c-3p was remarkably down-regulated in EC cells.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…CCNA2 (cyclin A2) is a cyclin accumulated in G1 phase and plays a regulatory role in the transitional period of G1/S and G2/M (Krasnov et al, 2017). Published literature has reported that CCNA2 functions on various cancers, like colorectal cancer (Huang et al, 2017), liver cancer (Yang et al, 2016), breast cancer (Gao et al, 2014), cervical cancer , and EC (Ma, 2019). In the present study, we found that miR-29c-3p was remarkably down-regulated in EC cells.…”
Section: Introductionsupporting
confidence: 52%
“…Prior studies have found that CCNA2, a type of cyclin, is able to promote cell proliferation, migration and invasion (Ma, 2019;Shekhar et al, 2019;Tu et al, 2019), as well as associated with various biological pathways like p53 signaling pathway (Zhang et al, 2018;Doan et al, 2019). In order to investigate the underlying mechanism of CCNA2 on EC cells, cells were classified into four groups: si-NC + DMSO, si-CCNA2 + DMSO, si-NC + PFTβand si-CCNA2 + PFTβ groups [PFTβ, p53 inhibitor, HY-16702, MedChemExpress, 10 µM (Da Pozzo et al, 2014)].…”
Section: Ccna2 Silencing Regulates the Migration Invasion And Cell Cmentioning
confidence: 99%
“…Many such studies have been published so far, which reveal miRNAs as tumor suppressors or oncogenes (Table 1). For example, miR-146a, miR-133b, miR-106b-3p, miR-219-5p, miR-206, miR-384, miR-455-5p, miR-128, miR-145-3p/5p, miR-10b-3p, miR-874-3p, miR-10a, miR-365, miR-301a, miR-6775-3p, miR-139-5p, miR-516b, miR-449a-5p, miR-125b, miR-433-3p, miR-370, miR-133b, miR-30a-3p/5p, miR-34a, miR-196a, and miR-125b-5p have been shown to act as tumor suppressors by inhibiting ESCC cell proliferation, promoting apoptosis by directly targeting oncogenes, or antagonizing pro-cancer signaling pathways [29,33,35,[40][41][42][43][44][45][46][47][48][49][50][51][52][54][55][56][57][58][60][61][62][63]110,133]. In contrast, pro-oncogenes such as miR-141, miR-21, miR-10b-3p, miR-424, miR-675-3p, miR-543, miR-135, miR-23b-3p, miR-502, miR-21-5p, and miR-548k have been reported to play contrasting roles in promoting cell proliferation or suppressing apoptosis in ESCC [47,[64][65][66][67][68][69][70][71][72][73].…”
Section: Non-coding Rnas Regulate Cell Proliferation and Apoptosis Dumentioning
confidence: 99%
“…For example, miR‐133b has been shown to suppress ESCC cell proliferation and invasion by inhibiting the expression of TAGLN2 . MiR‐219‐5p has been reported to inhibit cell cycle progression and cell proliferation in ESCC cell lines by downregulating the expression of CCNA2 (also known as CyclinA2) . In addition to regulating the infiltration and metastasis of cancer cells, abnormal expression of miRs is reportedly responsible for the development of cisplatin resistance in cancer cells .…”
Section: Introductionmentioning
confidence: 99%